Posterior Horn Lateral Meniscal Root Repair Via Double-Tunnel Transtibial Pullout With Meniscocapsular Release - Morgan D. Homan DO; Rafat H. Solaiman BA; Jacob A. Braaten BA; Nicholas I. Kennedy MD; Robert F. LaPrade MD, PhD (SAGE Publishing, 2023)
Background: Lateral meniscal root tears often occur in the acute setting in concert with anterior cruciate ligament (ACL) tears. Severe changes in tibiofemoral biomechanics and joint degeneration are encountered when these injuries are either unrecognized or are treated with meniscectomy; therefore, meniscal root surgical repair is now preferred for longer-term benefits. The most common repair techniques include side-to-side and transtibial pull-out repair, which may be performed via single or double transtibial tunnel techniques. Indications: The primary indication for lateral meniscal root repair with double transtibial tunnels is suspicion for a lateral meniscal root tear based upon injury mechanism, physical examination findings, magnetic resonance imaging findings, and confirmation with diagnostic arthroscopy. Technique Description: The root attachment site is decorticated. Adhesions that cause lateral meniscal root retraction are arthroscopically released. Two separate transtibial tunnels are drilled 5 mm apart from the anterolateral tibia, entering the anterolateral tibia distal to Gerdy's tubercle and entering the joint at the decorticated lateral root attachment site. Two suture tapes are passed through the torn lateral meniscal root in a vertical mattress configuration and shuttled with a passing suture through the tibial tunnels. The suture tapes are tied over a surgical button on the anterolateral tibia with the knee flexed to approximately 90° while the repair is viewed arthroscopically. Results: Lateral meniscal root repairs are safe and have very low reoperation rates. It has been reported that the transtibial pullout repair technique of the lateral meniscus significantly decreases lateral meniscus extrusion compared with other repair techniques in patients with combined ACL reconstruction. Zhuo et al also reported significantly improved postoperative clinical outcomes compared with the preoperative state in patients who underwent pullout repair for posterior lateral meniscal root avulsion tears. Discussion/Conclusion: The biomechanical and clinical evidence supports concomitant lateral meniscal root repair in the setting of concurrent ACL injury, and no studies to date have demonstrated a clear harm associated with this procedure. In addition, failure to repair the lateral meniscal root places supraphysiologic loads on the ACL graft and may increase the risk of graft failure. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.